2010
DOI: 10.1111/j.1742-4658.2010.07622.x
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of coenzyme Q‐deficient yeast by coenzyme Q analogues requires the isoprenoid side chain

Abstract: The ubiquinone coenzyme Q (CoQ) is synthesized in mitochondria with a large, hydrophobic isoprenoid side chain. It functions in mitochondrial respiration as well as protecting membranes from oxidative damage. Yeast that cannot synthesize CoQ (ΔCoQ) are viable, but cannot grow on nonfermentable carbon sources, unless supplied with ubiquinone. Previously we demonstrated that the isoprenoid side chain of the exogenous ubiquinone was important for growth of a ΔCoQ strain on the nonfermentable substrate glycerol [J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…This effect of supplementation with exogenous Q 6 is known to require uptake; Q 6 binds to soluble proteins derived from peptone in the growth medium and is taken up by cells and transported to mitochondria via an endocytic pathway [84]. James et al, [85] identified 16 yeast ORFs required for utilization of exogenous Q 4 in a yeast double knockout library ( ΔORFΔcoq2 ). We determined the steady-state levels of the Coq4, Coq7, and Coq9 polypeptides as indicators of the CoQ-synthome, and scanned for Q 6 -intermediates by HPLC tandem mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of supplementation with exogenous Q 6 is known to require uptake; Q 6 binds to soluble proteins derived from peptone in the growth medium and is taken up by cells and transported to mitochondria via an endocytic pathway [84]. James et al, [85] identified 16 yeast ORFs required for utilization of exogenous Q 4 in a yeast double knockout library ( ΔORFΔcoq2 ). We determined the steady-state levels of the Coq4, Coq7, and Coq9 polypeptides as indicators of the CoQ-synthome, and scanned for Q 6 -intermediates by HPLC tandem mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology used was a combination of previously described methods [39][40][41]. Briefly, LUVETs (large unilamellar vesicles produced by extrusion) were created from 25 mg/mL L-α-phosphatidylcholine (PC) from soybean (Type III-S, Millipore-Sigma) in chloroform, supplemented with 1-pyrene dodecanoic acid (Pyr12, Santa Cruz Biotechnology) to achieve a final concentration of 4 µM.…”
Section: Determination Of Coq6 Movement In Mixed Vesicle Populationsmentioning
confidence: 99%
“…After 90 s, 0.5 mL of a CoQcontaining vesicle population was added and the fluorescence was monitored for a total of 10 min. CoQ collisionally quenches Pyr12 fluorescence if both are present in the same vesicle and are capable of physical interaction [39,42]. On mixing the two populations of vesicles, a further decrease in the fluorescence signal can only occur if the CoQn isoform is able to move from vesicle to vesicle.…”
Section: Determination Of Coq6 Movement In Mixed Vesicle Populationsmentioning
confidence: 99%
See 2 more Smart Citations